Surface-Modified Sewage Sludge-Derived Carbonaceous Catalyst as a Persulfate Activator for Phenol Degradation - Meiling Han (International Journal of Environmental Research and Public Health, 2020)
In this study, a catalytic persulfate oxidation process comprising sodium persulfate (PS) and modified sewage sludge-derived carbonaceous catalysts was tested for the degradation of phenol. Sludge-based biochar was modified by high-temperature treatment combined with hydrochloric acid oxidation. The surface properties of carbonaceous catalysts before and after modification were characterized by elemental analysis, N2 isothermal adsorption-desorption, scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. The effects of reaction parameters including catalyst dosage, PS/phenol molar ratio, initial pH and reaction temperature on the degradation rate of phenol were investigated. The kinetics of phenol transformation was explored and the reaction rate appeared pseudo first-order kinetics. In SS-600-HCl/PS system, 91% phenol could be efficiently degraded under certain reaction conditions ([phenol]0 = 100 mg/L, catalyst dosage = 0.8 g/L, PS/phenol molar ratio = 3/1, pH = 7, 25 °C) in 180 min. Thus, the results showed that the modified sewage sludge-derived carbonaceous catalyst had a better ability to activate PS for phenol degradation.